Knowledge mapping methodology for developing a knowledge management system: a case study in Universiti Teknologi MARA Kelantan / Khalid Abdul Wahid and Mohd Nasir Ismail - Wahid, Khalid Abdul; Ismail, Mohd Nasir (2006)
Knowledge map approach represents tacit and explicit knowledge in an organization. Knowledge is created and reused during the execution of a business processes going through the business process and dealing with specific relevant knowledge for a particular task of process. A knowledge map is the visual representation of captured information and relationship, which enables the efficient communication and learning of knowledge by observers with different backgrounds at multiple levels of detail. The map consists of text, graphics, stories, models or numbers. Knowledge mapping serves as the continuously evolving corporate memory, capturing and integrating the key knowledge of an organization. It enables people learning through navigation and interrogation of the information in the map and also through the creation of new knowledge through the discovery of new relationships. This paper suggests the methodology for capturing and representing organizational knowledge. The methodology is comprised of a six-step procedure from defining an organizational knowledge step to a knowledge map validation step. A case study of UiTM Kelantan campus is also provided at the end of the discussion to verify the proposed methodology focusing only on the process of the verificatiol1 of subject offered as a part for the subject registration process and finally discusses the lesson learned from which the knowledge mapping methodology is implemented.